2015
DOI: 10.1063/1.4906322
|View full text |Cite
|
Sign up to set email alerts
|

Switching of perpendicular exchange bias in Pt/Co/Pt/α-Cr2O3/Pt layered structure using magneto-electric effect

Abstract: Switching of the perpendicular exchange bias polarity using a magneto-electric (ME) effect of α-Cr2O3 was investigated. From the change in the exchange bias field with the electric field during the ME field cooling, i.e., the simultaneous application of both magnetic and electric fields during the cooling, we determined the threshold electric field to switch the perpendicular exchange bias polarity. It was found that the threshold electric field was inversely proportional to the magnetic field indicating that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
65
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(74 citation statements)
references
References 25 publications
7
65
2
Order By: Relevance
“…This ability to switch the sign of α is a consequence of the reduced Cr 2 O 3 thickness, where the total Zeeman energy associated with the surface magnetization in Cr 2 O 3 becomes comparable to the total ME energy associated with the crystal volume. This conclusion explains previous results [8,[11][12][13] of the electric switching of the exchange bias field in all thin film systems (0001) Cr 2 O 3 /[Co/Pt] n , where it was found that much higher field products E fc H fc are required to achieve the switching compared to bulk single crystals of Cr 2 O 3 .…”
Section: Introductionsupporting
confidence: 79%
See 4 more Smart Citations
“…This ability to switch the sign of α is a consequence of the reduced Cr 2 O 3 thickness, where the total Zeeman energy associated with the surface magnetization in Cr 2 O 3 becomes comparable to the total ME energy associated with the crystal volume. This conclusion explains previous results [8,[11][12][13] of the electric switching of the exchange bias field in all thin film systems (0001) Cr 2 O 3 /[Co/Pt] n , where it was found that much higher field products E fc H fc are required to achieve the switching compared to bulk single crystals of Cr 2 O 3 .…”
Section: Introductionsupporting
confidence: 79%
“…The largest field product of |H fc | = 50 kOe and |E fc | = 60 kV cm −1 was not successful, while the films were destroyed for E fc 80 kV cm −1 due to a dielectric breakdown. The lower breakdown field value when compared to previous reports [8,[11][12][13] is likely due to the larger electrode size in our case.…”
Section: Resultscontrasting
confidence: 53%
See 3 more Smart Citations